Diversity of culturable bacteria capable of degrading hydrocarbons from the beach of Caleta Córdova, Argentina - Pucci, Graciela N. (2010)
Inter-tidal sediments and marine water from Caleta Córdova, a beach in the north of Comodoro Rivadavia, Argentina, were analyzed. Three sites were sampled each season between 2006 and 2006. The first site is a public beach, the second site is near a fishing port and the third one near an oil buoy. Bacterial communities were determined based on differences in the composition of membrane fatty acids, identification of bacteria were using the MIDI Sherlock system, and the potential of communities for the use of hydrocarbons through the mineralization of gasoline, kerosene, diesel, crude oil and mineral oils. Mineralization showed a capacity of the microorganisms to use the hydrocarbons in only two sites of study. Of 251 strains were analyzed and the system could identify 24 genera and 40 species in only 124 strains. The rest of strains were not found in Sherlock data base (version 6.0). Pseudoalteromonas was the genus that was more frequently isolated.